2019
DOI: 10.1101/531657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centering based on active diffusion in mouse oocytes is non-specific

Abstract: The mechanism for nucleus centering in mouse oocytes results from a gradient of actin-positive vesicles. By microinjecting oil droplets and fluorescent beads, we analyze the consequences of the gradient of activity on transport of exogenous tracer particles of different sizes. We also use optical tweezers to probe rheological properties of the cytoplasm. We find that the gradient activity induces a general centering force, akin to an effective pressure gradient, leading to centering of oil droplets with veloci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Recently, Hurst et al used the same OT system to probe internalized microbeads and revealed the strong softening and fluidification of the cytoplasm during mitosis [45]. More excitingly, instead of manipulating internalized microbeads via OT, Colin et al probed endogenous vesicles in the cytoplasm with sinusoidal forces and successfully measured the intracellular shear modules [44]. Their observation revealed that the actin mesh exerts a pressure-gradient-like force, which moves the nucleus from the periphery to the center in both Prophase I and Meiosis I.…”
Section: Cytosolic Micro-rheologymentioning
confidence: 99%
“…Recently, Hurst et al used the same OT system to probe internalized microbeads and revealed the strong softening and fluidification of the cytoplasm during mitosis [45]. More excitingly, instead of manipulating internalized microbeads via OT, Colin et al probed endogenous vesicles in the cytoplasm with sinusoidal forces and successfully measured the intracellular shear modules [44]. Their observation revealed that the actin mesh exerts a pressure-gradient-like force, which moves the nucleus from the periphery to the center in both Prophase I and Meiosis I.…”
Section: Cytosolic Micro-rheologymentioning
confidence: 99%